Relationship between Local Government Commitment and Digital Public Service Implementation Under Prabowo Subianto - Dodi Rahmat Setiawan (Goodwood Publishing, 2026)
Purpose: This study investigates how the organizational commitment of local governments is linked to the adoption of digital public services in the first year of President Prabowo Subianto administration (2024-2025). Methodology: The explanatory approach to quantitative research was applied in the current study with references to primary data obtained via local government officials and secondary data provided by UN E-Government Survey 2024. Simple linear regression was employed to determine the impact of organizational commitment on the digital implementation of public services. Results: The findings revealed a positive and statistically significant correlation between organizational commitment and digital public service implementation (ß = 0.642; p = 0.001), with a coefficient of determination (R2) of 0.535. This outcome indicates that the more committed an organization is, the more local government officials increase the effectiveness, transparency, and efficiency of digital public services. Conclusions: To successfully digitalize local government, supportive work culture, adaptive leadership, and building digital capacity should be concepts that strengthen organizational commitment. Limitations: In this research, the regions considered are selected, and the first year of the administration of Prabowo Subianto is considered, thereby limiting generalization. Contributions: This study provides empirical data on how commitment to the organization is a critical predictor of digital public service execution in the initial stages of the current Indonesian government.